"What kind of doctor do you want to become?": Clinical supervisors' perceptions of their roles in the professional identity formation of General Practice residents. (4th May 2023) - Barnhoorn, Pieter C.; Nierkens, Vera; Numans, Mattijs E.; Steinert, Yvonne; van Mook, Walther N. K. A.
Abstract: Purpose: Supporting the development of a professional identity is a primary objective in postgraduate education. Few empirical studies have explored professional identity formation (PIF) in residency, and little is known about supervisors' perceptions of their roles in residents' PIF. In this study, we sought to understand how supervisors perceive their roles in the PIF of General Practice (GP) residents. Materials and methods: Guided by principles of qualitative description, we conducted eight focus groups with 55 supervisors at four General Practice training institutes across the Netherlands. Informed by a conceptual framework of PIF, we performed a thematic analysis of focus group transcripts. Results: Three themes related to how GP supervisors described their roles in supporting residents' PIF: supervising with the desired goal of GP training in mind; role modeling and mentoring as key strategies to achieve that goal; and the value of developing bonds of trust to support the process. Conclusions: To our knowledge, this study is the first to explore PIF in GP training from the perspective of clinical supervisors. The identified themes mirror the components of the therapeutic alliance between doctors and patients from a supervisor's perspective and highlight the pivotal roles of the supervisor in a resident's PIF.